2020
DOI: 10.1186/s12889-020-08804-4
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and its effect on chronic disease prevention: evidence from China’s data

Abstract: Background: Improving health literacy is an important public health goal in many countries. Although many studies have suggested that low health literacy has adverse effects on an individual's health outcomes, confounding factors are often not accounted. This paper examines the interplay between health literacy and chronic disease prevention. Methods: A population-based sample of 8194 participants aged 15-69 years old in Ningbo were used from China's 2017 National Health Literacy Surveillance Data. We use mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 19 publications
(43 reference statements)
8
91
1
1
Order By: Relevance
“…Among the participants, those with lower health literacy levels were more likely to be male, older, poorer, less educated, and suffering from chronic diseases. This is consistent with the research results of Liu L [1] , Verney SP [9] , S rensen K [25] and other scholars.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the participants, those with lower health literacy levels were more likely to be male, older, poorer, less educated, and suffering from chronic diseases. This is consistent with the research results of Liu L [1] , Verney SP [9] , S rensen K [25] and other scholars.…”
Section: Discussionsupporting
confidence: 92%
“…1 Background "Health literacy", proposed in 1974, is playing an increasingly important role in the eld of public health [1] .…”
Section: Resultsmentioning
confidence: 99%
“…Our data come from a sub-sample of the National Health Literacy Surveillance (NHLS) conducted in Ningbo, in 2018 and 2019 (see [ 13 ], for an overview on NHLS). Ningbo, located in the Yangtze River Delta in South China, was ranked the world’s fourth-largest port city in 2013 [ 14 ], and it is an important commercial and financial centre in South China.…”
Section: Methodsmentioning
confidence: 99%
“…We used a stratified, multi-stage probability proportional to population size (PPS) sampling frame. For details, please refer to our earlier publication in [ 13 ]. We pooled the observations from the 2018 survey (covering 10 counties, 43 streets, 242 villages/communities involving 6581 individuals) and 2019 survey (covering 10 counties, 45 streets, 124 villages/communities involving 6340 individuals), and obtained a total sample of 12,921 respondents.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study from China found that the fatality rate of men with the virus was approximately 65% higher than that of women [ 21 ]. Although there are uncertain explanations for this pattern as the earlier work suggests that cardiovascular disease rate (i.e., high blood pressure), and unhealthy or unsafe habits (i.e., smoking) among men is higher than women [ 22 ], - immune response is also different in the two genders [ 21 ]. Males also tend to suffer from the SARS disease more seriously than women, which may partially explain disparities in gendered use of tobacco [ 23 ].…”
Section: Gender and Pandemicsmentioning
confidence: 99%